The botanical image in the post-photographic era: How to face the biodiversity crisis? How can art contribute? - Casanova Rodríguez, Ramón; Guixà Frutos, Ricardo; Rosado Rodrigo, Pilar (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article is a review of the ability of photographic herbariums to establish experimental alliances with potential to help raise awareness and resolve the plant biodiversity crisis. It analyzes how the photographic medium, under the prism of artistic creation, can be erected as a revealing system, able to overcome the mere description and expand the cognitive limitations of our visual perception, revealing the complexity of the botanical universe through a deeper and poetic look at its physical nature.